Edaphic filters as abiotic drivers of Myrtaceae assemblages in subtropical Araucaria Forest - Stedille L.I.B.* (2020)
© 2020, Springer Nature Switzerland AG.Aims: This study investigated whether soil chemistry act as abiotic drivers of Myrtaceae assemblages, and also investigated the occurrence of indicator species. Methods: We first characterize the edaphic conditions of forest fragments occupied by Myrtaceae assemblages in Subtropical Araucaria Forest. Then, we investigated the association between soil chemistry and the structure of the assemblages. Finally, we verified which Myrtaceae species are chemical-edaphic bioindicators. Results: We measured 2357 individuals belonging to 26 species from the Myrtaceae family. The Myrtaceae assemblages were predominantly composed by populations with aggregate spatial distribution pattern. This spatial behavior reflects their edaphic requirements because the soil conditions are heterogeneous even on a small scale, forming chemical-edaphic niche patches. Ecological dominance occurred in habitats characterized by restrictive environmental factors such as soils with high acidity and high availability of exchangeable aluminum. Acca sellowiana and Campomanesia xanthocarpa are indicator species of fertile soils, while Myrceugenia regnelliana is acid and low fertility soils indicative. Conclusions: In this study we show that soil acidity is an effective driver of Myrtaceae assemblages in Subtropical Araucaria Forest and the use of Myrtaceae indicators can enable policymakers and environmental inspectors to more easily enact conservation in Brazilian ecosystems.